Fibula, Fabula, Fact (Volume 18.0) (Finnish Literature Society / SKS, 2014)
"The chapters of Fibula, Fabula, Fact – The Viking Age in Finland are intended to provide essential foundations for approaching the important topic of the Viking Age in Finland. These chapters are oriented to provide introductions to the sources, methods and perspectives of diverse disciplines in a way that is accessible to specialists from other fields, specialists from outside Finland, and also to non-specialist readers and students who may be more generally interested in the topic. Rather than detailed case studies, the contributors have sought to negotiate definitions of the Viking Age as a historical period in the cultural areas associated with modern-day Finland, and in areas associated with Finns, Karelians and other North Finnic linguistic-cultural groups more generally. Within the incredible diversity of data and disciplines represented here, the Viking Age tends to be distinguished by differentiating it from earlier and later periods, while the geographical space is quite fluidly defined for this era, which was long before the construction of modern nations with their fenced and guarded borders. Most significantly, the contributions lay emphasis on contextualizing the Viking Age within the complexities of defining cultural identities in the past through traces of cultural, linguistic or genetic features. The volume opens with a general introduction to the topic that is intended to provide a frame of reference for discussion, paralleled by a closing afterward. The following chapters are organized according to three thematic sections which reflect the three aspects of any discussion of the Viking Age in Finland: Time, Space, and People – because any discussion of the ‘Viking Age’ in ‘Finland’ is necessarily concerned with individuals, societies and cultures."